Does the Sector Matters? An Empirical Investigation of Job Satisfaction and Performance Evaluation Process Based on Romanian Employees’ Perceptions - Alexandra BEIU; Adriana Ana-Maria DAVIDESCU (Revista de Management Comparat International)
The paper aims to investigate if the activity sector matters in explaining and analysing the job satisfaction, its determinants and also the satisfaction related to the performance evaluation process using an empirical research based on gender differences for a sample of 301 employees from seven sectors of activity. The paper aims to respond to the following key research questions: there are statistical differences concerning the job satisfaction and also the perceptions regarding the performance evaluation process in different sectors of activity with certain specificities? In order to respond to these questions, descriptive statistics, non-parametric correlation and non-parametric tests (Kruskal-Wallis) were used. The empirical results revealed that employees from services, manufacturing industry and agriculture exhibited the highest level of job satisfaction while constructions represents the sector with the lowest level. The analysis of motivational factors revealed that workplace comfort and job stability are considered to be the most important motivating factors in all sectors of activity, while the perspective of hierarchical advancement and logistical support the least motivating. The results of Kruskal-Wallis test pointed out statistical differences among sectors of activity regarding the job satisfaction level and the attractiveness of work done. Concerning the level of satisfaction related to the last employee evaluations, retail trade and manufacturing industry are the sector with the highest degree of satisfaction while services and wholesale trade registered lower levels of satisfaction. As methods used in the evaluation, the analysis based on the superiors’ opinion was used in all sectors with the exception of agriculture characterized by the presence of informal free talks. The empirical results highlighted significant differences in different sectors of activity regarding the elements taken into consideration in the employee performance evaluation process: productivity, initiative/innovation, quality of communication, relationships with subordinates, superiors and customers and professional development.